2013
DOI: 10.1161/strokeaha.111.000745
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Risk Factors Are Not Major Contributors to the Variance in Carotid Intima-Media Thickness

Abstract: Background and Purpose Carotid Intima-Media Thickness (cIMT) was a widely accepted ultrasound marker of subclinical atherosclerosis in the past. Although traditional risk factors may explain approximately 50% of the variance in plaque burden, they may not explain such a high proportion of the variance in IMT, especially when measured in plaque free-locations. We aimed this study to identify individuals with cIMT unexplained by traditional risk factors for future environmental and genetic research. Methods As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
3
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 56 publications
6
60
3
8
Order By: Relevance
“…Although these are still relatively low values, our analyses resulted with higher R 2 coefficients compared with the previous work by Rundek et al 15 Some population characteristics can explain different results between the 2 studies. Models including only age and race as explanatory variables in ELSA-Brasil yielded higher R 2 coefficients (≤0.298, Table II in the online-only Data Supplement) than the R 2 coefficients yielded in NOMAS.…”
Section: Discussioncontrasting
confidence: 80%
“…Although these are still relatively low values, our analyses resulted with higher R 2 coefficients compared with the previous work by Rundek et al 15 Some population characteristics can explain different results between the 2 studies. Models including only age and race as explanatory variables in ELSA-Brasil yielded higher R 2 coefficients (≤0.298, Table II in the online-only Data Supplement) than the R 2 coefficients yielded in NOMAS.…”
Section: Discussioncontrasting
confidence: 80%
“…Even a large population-based study on carotid intima media thickness demonstrated that only 16% of the variance in the anatomical imaging data could be explained by a final multivariable model containing adiponectin and 9 traditional risk factors such as body mass index and smoking. 30 There are several limitations to be considered in interpreting our results (please refer to the Supplementary Discussion for more information). Further studies with a larger sample size are required to confirm if exercise training could actually decrease WD-mediated plaque vulnerability to rupture by attenuating matrix disorganization that includes degradation of collagen, through the mechanism proposed in this study (i.e., exercise-mediated anti-atherosclerotic modulation of the adiponectin/resistin/VCAM-1-related systemic cytokine network, culminating in the reduction of monocytes/macrophage recruitment, M1/M2 ratio, and MMP activity in atheromatous arteries).…”
Section: Discussionmentioning
confidence: 99%
“…As other unmeasured determinants, the difference in access to medical care, difference in socioeconomic status 31,32) , difference in psychological factors 33) , difference in other environmental factors 34) , frequency, and intensity of physical activity 35) could be involved.…”
Section: Sex-specific Determinants: Ldl-cholesterol and Non-hdl-cholementioning
confidence: 99%